Spatial variability of soil nutrients under the rice-fallow system of eastern India using geostatistics and Geographic Information System - GANGOPADHYAY, S.K.; REDDY, G.P. OBI (Journal of Soil and Water Conservation, 2022)
The study aimed to assess the spatial variability of soil nutrients under the rice-fallow system in eastern India using geostatistics and Geographic Information System (GIS). In the investigation, 88 surface soil samples (0-25 cm) were collected at grid interval of 1000×1000m2 and determined soil organic carbon (SOC), available Nitrogen (N), Phosphorous (P), Potassium (K) and micronutrients viz., Copper (Cu), Iron (Fe), Manganese (Mn) and Zinc (Zn). The analysis shows that OC, N, P, K, Cu, Fe, Mg and Zn varies from 0.18 to 1.42%, 139.00 to 589.00kg ha-1, 0.80 to 31.60 kg ha-1, 40.00 to 353.00 kg ha-1, 3.0 to 5.60 mg kg-1, 13.00 to 320.0 mg kg-1, 4.10 to 141.80 mg kg-1, and 0.10 to 4.70 mg kg-1, respectively. Geostatistical analysis shows that the Exponential model was found to be the best fit for soil OC and Mn, Gaussian model for available N and P, the Spherical model for available K and circular model for Fe, and Zn. The spatial variability in soil nutrients is attributed to underlying parent material, soil management and land use practices of the study area. The results obtained help in site-specific soil nutrient management, improve soil structure and soil fertility in the rice-fallow system of the study area.